Induction Motor Drive based on Efficiency Optimisation andDrive Loss Minimization in Real-Time Control of Linkage Flux of Drive Reference - Farshid Abdolahnejad Baroogh; Milad Gheydi; Payam Farhadi (International Journal of Advances in Applied Sciences, 2017)
Induction motor drives are commonly used for applications with vast variations in mechanical load for torques under nominal values. HVAC loads are among these loads. The most ideal scheme for induction motor drive design should include drive loss reduction, or efficiency improvement, proportional to load torque such that optimal performance of drive is not affected. In this paper, using analytical methods, an accurate model is proposed for induction motor drive design. This model allows us to utilize real control and classical control theory for better performance of drive control system. The most damaging mechanical load for induction motor drive is impulse load or so-called periodic load. A scheme proposed for power loss control includes loss control for this type of load, meanwhile, robustness of drive system and stator frequency stability are retained. Main advantages for this scheme are applicability and implementation on various induction motor drives with various powers, without any specific requirements and the least possible computation for the processors.